Analiza tokovnih struktur v vstopnem sistemu motorjev - primerjava rezultatov meritev in numerične simulacije - Rodman Oprešnik, Samuel (Strojniški vestnik, 2005)
A comparison and analysis of laser Doppler anemometry (LDA) measurements and acomputed fluid dynamics (CFD) simulation of the in-cylinder flow structures generated by an engine induction system is presented in this paper. An octagonal glass model with a moving piston complementary to a real engine cylinder was applied in the analysis. Good agreement between the measured and simulated patterns of the flow structures and the inlet-valve discharge coefficients was obtained. In general, this study shows that in-cylinder CFD predictions yield reasonably accurate results that help to improve the knowledge of the air-flow characteristics during the intake stroke. CFD therefore represents an effective design tool for developing less-polluting and more efficient internal combustion engines.
Keywords: motorji ZNZ; računalniška dinamika tekočin; CFD; polja hitrostna; anemometri Dopplerjevi laserski; motorji z notranjim zgorevanjem; dinamika tekočin; numerična simulacija; vbrizgavanje goriva